2018
DOI: 10.3389/fnmol.2018.00330
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Details of Retinal Guanylyl Cyclase 1/GCAP-2 Interaction

Abstract: The rod outer segment guanylyl cyclase 1 (ROS-GC1) is an essential component of photo-transduction in the retina. In the light-induced signal cascade, membrane-bound ROS-GC1 restores cGMP levels in the dark in a calcium-dependent manner. With decreasing calcium concentration in the intracellular compartment, ROS-GC1 is activated via the intracellular site by guanylyl cyclase-activating proteins (GCAP-1/-2). Presently, the exact activation mechanism is elusive. To obtain structural insights into the ROS-GC1 reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…While it is clear that both GCAPs can regulate GC1 over the narrow physiological window of intracellular Ca 2+ , quite different mechanisms have been proposed for the regulation. Some studies support distinct binding interfaces between GC1 and GCAP1/GCAP2, the first GCAP being located at the juxtamembrane region and the second prevalently bound to the catalytic-C terminal domain 2931 , thus allowing the binding of GCAP1 and GCAP2 to either the same or distinct GC1 molecules, but always in different interfaces On the other hand, other studies found a partly overlapped GC interface for GCAP1 and GCAP2 32,33 , suggesting a competition between GCAP1 and GCAP2 for GC1 activation in mouse cones 34 as well as in rods. Overall, GCAPs seem to operate in a “calcium-relay” mode, thus acting simultaneously on either the same or distinct GC1 molecules to induce gradual responses in terms of cGMP synthesis triggered by small changes in intracellular [Ca 2+ ] 3,35 .…”
Section: Introductionmentioning
confidence: 99%
“…While it is clear that both GCAPs can regulate GC1 over the narrow physiological window of intracellular Ca 2+ , quite different mechanisms have been proposed for the regulation. Some studies support distinct binding interfaces between GC1 and GCAP1/GCAP2, the first GCAP being located at the juxtamembrane region and the second prevalently bound to the catalytic-C terminal domain 2931 , thus allowing the binding of GCAP1 and GCAP2 to either the same or distinct GC1 molecules, but always in different interfaces On the other hand, other studies found a partly overlapped GC interface for GCAP1 and GCAP2 32,33 , suggesting a competition between GCAP1 and GCAP2 for GC1 activation in mouse cones 34 as well as in rods. Overall, GCAPs seem to operate in a “calcium-relay” mode, thus acting simultaneously on either the same or distinct GC1 molecules to induce gradual responses in terms of cGMP synthesis triggered by small changes in intracellular [Ca 2+ ] 3,35 .…”
Section: Introductionmentioning
confidence: 99%
“…XLMS experiments on complex protein mixtures usually yield thousands of cross-links, making the inspection of individual spectra impossible. Recently, DSBU and MeroX have been combined for developing XLMS workflows to study isolated proteins or protein complexes. , …”
mentioning
confidence: 99%
“…GMP − PDEα1 and/or GMP − PDEα2 convert cGMP to GMP which closes the CNG ion channel. Conversely, ANPR1-like and ANPR1-like2 [64, 65] convert GTP to cGMP helping to regulate the opening and closing of CNG. Finally, transduction is terminated by arrestin deactivating metarhodopsin and phosphorylation of metarhodopsin by Rh kinase and GRK5-like.…”
Section: Discussionmentioning
confidence: 99%